EVALUASI KONDISI LINGKUNGAN PERAIRAN KAWASAN PULAU ABANG, GALANG BARU, BATAM BERDASARKAN ANALISA INDEKS STORET DAN SIMILARITAS CANBERA - Sachoemar., dkk, Suhendar I (BPPT)
Evaluation of the water quality status at Abang Island Region was conducted by using the STORET and Canbera Similarity Indeks during Mei, June and October 2006. Thes analysis result shows that the water quality within this region was within the range of good to moderate. This condition indicate that the water quality status is still suitable and support for living marine biotic organism. During May, water quality was good and decrease in June and October due to the additional of the organic material from the land surface driven by precipitation as response to monsoonal change.Keywords : water quality, Abang island, Storet Index, Similarity Index, Canbera.